2019
DOI: 10.1111/phn.12660
|View full text |Cite
|
Sign up to set email alerts
|

Access to clean water and urinary tract infections in Haitian women

Abstract: Objectives Access to clean water is a global concern. For women living in developing countries, the lack of clean water increases their risk of bacterial infections, such as a urinary tract infection (UTI). The purpose of this study was to examine if the location of water source has a relationship with the rate of UTIs in women who lived in the Léogâne area of Haiti. Design Descriptive, correlational, retrospective chart review used de‐identified data from medical intake flow sheets. Sample A total of 311 medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…The present study also observed that women who were using supply water (purified groundwater supplied through the municipal pipeline) for bathing and cooking purposes for a long period of time had more probability of having UTI than those who were using groundwater (directly from tube-well). Comparatively, this study denies the quite similar study reported in previous investigation of Andersen et al, 2019 who showed that pump water is responsible for UTI more than in short well water using participants. Since supply water is treated centrally, so it is thought to be much cleaner, and residents are not encouraged to boil before using.…”
Section: Discussioncontrasting
confidence: 58%
“…The present study also observed that women who were using supply water (purified groundwater supplied through the municipal pipeline) for bathing and cooking purposes for a long period of time had more probability of having UTI than those who were using groundwater (directly from tube-well). Comparatively, this study denies the quite similar study reported in previous investigation of Andersen et al, 2019 who showed that pump water is responsible for UTI more than in short well water using participants. Since supply water is treated centrally, so it is thought to be much cleaner, and residents are not encouraged to boil before using.…”
Section: Discussioncontrasting
confidence: 58%
“…Urinary tract infection (UTI) and bacterial vaginosis (BV) are caused by bacterial presence in the urinary tract and the vagina. 1 , 2 Factors, including water accessibility, 3 water quality, 4 , 5 , 6 and poor menstrual hygiene practices can contribute to the increased susceptibility to UTI and BV. 7 , 8 , 9 BV is one of the most prevalent infections among women of reproductive age worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in social determinants of health such as economic stability, healthcare, living conditions and education generally have been shown to improve health. 6 , 7 For instance, access to clean water has been shown to reduce bacterial infections and promote health and well-being, 8 and epidemiological research in Peru has argued for a distribution of social and economic development to address health issues. 9 However, because many of these factors have occurred at the same time (e.g.…”
Section: Introductionmentioning
confidence: 99%